Hubungan Antara Persepsi Terhadap Kualitas Produk Dengan Kepuasan Konsumen Pada Mahasiswa Fakultas Psikologi Universitas Muhammadiyah Surakarta Pengguna Smartphone Iphone - Claudia, Stevi; , Susatyo Yuwono, S.Psi, M.Si.,Psi (2017)
ABSTRACT Smartphone when it has been life style and needs of society in indonesia. The iphone is one of smartphone brands that has many advantages and differences compared with the other brands. Various strategy effected iphone could lead to the technology in indonesia and differentiation product is expected to satisfy customers. The satisfaction was largely determined by the customers' perception of the qualities of the product. The aim of this research is to find the correlation between perceptions of quality products with customer satisfaction iPhone users. The approximation method of this research is Quantitative was conducted on students of the Faculty Psychology of iPhone users in Muhammadiyah University Surakarta. A sample of 154 students was taken incidental to those found during the study. Perception of the quality products and customer satisfaction is measured using a Likert scale questionnaire that had been tested for validity and reliability. Data analysis technique used was Pearson's product moment correlation using SPSS 16 for Windows program. The results showed that the respondents' perceptions of the quality of the iPhone including moderate (mean score = 73,42; the scale range 61,6-78,4), while the level of satisfaction as well as moderate (mean score = 86,90; the scale range 72,6-92,4). There is a positive correlation between the perception of the quality product with the iPhone user satisfaction (rs = 0,786; p < 0,01). The conclusion drawn was the better perception of the quality product, the higher customer satisfaction. Therefore, it is advisable for the iPhone smartphone manufacturers to continue to maintain and improve the quality of its products and services in order to get a good response in order to satisfy the perception of consumers. Keywords: perceived quality, satisfaction, student, iPhone